PRAWO DO OBRONY W POSTĘPOWANIU PRZED MIĘDZYNARODOWYM TRYBUNAŁEM KARNYM - Wiliński, Paweł (Wydział Prawa i Administracji UAM, 2005)
In the study the author discusses the scope of the right to defence before the International Criminal Court, the first permanent criminal court with an international and universal jurisdiction, created to prosecute the most grevious crimes, including crimes against humanity, genocide and war crimes.When defining terms such as suspect and defendant, the author points to the differences in understanding their positions in trial. He lists and discusses the rights vested in the defendant in the course of proceedings and also presents the ways in which the ICC has developed the principles of a fair trial. Then, he reflects on the right to an attorney, the right to the assistance of a translator, principles of using provisional detention, rules of conduct when approving charges in preparatory proceedings, the defendant’s rights in judicial proceedings. He also discusses the right to free expression, the right to remain silent, the right to appeal against the sentence or other decisions taken in court. Having analysed the range of the defendant’s rights, the author arrives at the conclusion that they meet requirements of a fair trial in criminal proceedings. At the same time, he emphasises that such model of conduct is a combination of two different systems of law: common law and civil law. The practical exercise of the right to defence depends to a great extent on the way in which the Tribunal interprets and implements those institutions in its judicial decisions. This, on the one hand, gives a chance for better realisation of fair trial postulates, on the other hand however, it may pose a threat to such a trial.
THE RIGHT TO DEFENCE BEFORE THE INTERNATIONAL CRIMINAL COURT